Breaking barriers for Bangladeshi female solo travelers. (January 2022) - Bernard, Shaniel; Rahman, Imran; McGehee, Nancy Gard
Abstract: Asian Muslim women's travel habits are sorely under-researched. In response to various calls for research in this area, this study utilizes Hofstede's five cultural dimensions to determine how Bangladeshi cultural values inhibit and/or enhance travel constraints for solo Muslim female travelers and the subsequent effects on solo travel behavior. We propose solo travel as a strategic tourism development tool to achieve mobility rights and gender equality particularly for destinations that are highly populated with more women than men. Introducing an interpretivist qualitative approach, the study extracted both survey and open-ended responses from 307 frequent Bangladeshi solo travelers that were recruited from a women-only English-speaking Facebook Bangladeshi travel group. The findings reveal that this group is constrained by a unique combination of intrapersonal, interpersonal, and structural factors. Power-distance, masculinity, and uncertainty-avoidance also play key roles. Sustainable and practical applications are outlined for destination management organizations, travel planners, policy makers, non-governmental organizations, and for-profit tour companies that benefit both Bangladeshi solo female travelers and those with whom they interact. Highlights: The study showcases constraints for solo female travelers from Bangladesh. Intrapersonal, interpersonal, and structural factors constrain solo female travel. Power-distance, masculinity, and uncertainty-avoidance also play key roles. DMOs & travel planners can use findings to enhance solo female travel experiences.